Relation between organizational capacity for change and readiness for change - Irena Mladenova (Administrative Sciences, 2022)
Readiness for change is seen as an important prerequisite increasing chances for change success. While assessing the readiness level allows for tailoring of the interventions and the change process, it requires time and planning. When organizations face increasing levels of unpredictability and need to adapt to fast environmental shifts, linear causal models to plan and implement changes become harder to follow. Emergent changes also barely accommodate planning and assessing readiness levels. Multiple and overlapping change initiatives become the norm rather than an exception, thus exert additional pressure on organizations hoping to start with assessing and developing readiness. Applying dynamic capabilities lens allows addressing such challenges through the concept of organizational capacity for change. This article reviews theoretical and empirical research advances to answer two questions. First, how do readiness and organizational capacity for change differ? A review of theoretical assumptions, dimensions and antecedents is employed to delineate the two constructs. Second, what is the relationship between the two constructs? The analysis is guided by an organizational change typology to highlight their applicability to selected types of change. The research concludes that capacity for change differs and can complement readiness in helping organizations navigate unpredictable environments.
Keywords: 350; organizational capacity for change; organizational change; readiness for change